(untitled) (Eurasian Scientific Herald, 2022)
This article discusses the preparation of pupils for school based on the development of their emotional cognition and motor skills. The author, relying on pedagogical data, archival documents and written sources, analyzed the problem on the basis of the available scientific literature and studied the existing specific aspects of preparing pupils for school based on emotional cognition and the development of motor skills.